Quantum quadratic-attractive plus quartic repulsive potential in a box - Aguilera-Navarro, V. C.; Koo, E. L.; Zimerman, A. H.; Iwamoto, H. (IOP Publishing, 1982)
The solution of the Schrodinger equation for the two well oscillator in a symmetric box is formulated exactly, and high-accuracy numerical results are obtained for the lowest states. Perturbative solutions for boxes whose walls are (i) fairly close to each other, (ii) in the vicinity of the inflection points of the potential, (iii) at the position of the minima of the potential, and (iv) very far from each other are also obtained and compared with the exact ones.